Merilni sistem za vrednotenje živčno-mišičnih funkcij trupa - Šarabon, Nejc (Šport (Ljubljana), 2013)
Low back pain is one of the most common health problems nowadays. In the individuals with low back pain numerous alterations in neuromuscular functions of the trunk can be observed. Aetiology of low back pain is complex and often depends on psychosomatic status. Therefore, it is important to understand the biomechanical characteristics, which are altered in low back pain patients. Objective assessment of these alterations allows detection of acause or a consequence of low back pain. Even though studies demonstrated changes in neuromuscular functions of the trunk in low back pain patients, is this kind of assessment limited to the research and is not used in a clinical practice. The purpose of this paper is to present the technical characteristics of the integrated measurement system for valid and objective assessment of the trunk neuromuscular functions, which was developed as part of the research project carried out between the university and the industry. We also empirically and graphically present a case study of one whole measurement on a young healthy person. At the end of the paper we discuss practical solutions for health and sport institutions when treating low back pain patients.
Keywords: bolečina v križu; diagnostika; gibalna terapija; hrbtenica; inovativnost; meritve